The Multiplier Algebra of Orlicz Spaces - Abdallah Hakawati (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In this paper we prove that if ? is a modulus function and if X = [0,1] is given the Lebesgue measure, then M(L?) = L?, if and only if lim x – 0 ?(x2)/ ?(x) < ?; L? being the Orlicz space L? (X); and M(L?) its multiplier algebra.